Perancangan dan Implementasi Sistem Pengelolaan Pencatatan Barang DPPESDM Berbasis Web - Umri, Chairil; Sembiring, M. Miko Sahputra (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The management of regional assets at the Department of Industry, Trade, Energy, and Mineral Resources (DPPESDM) of North Sumatra Province faces significant challenges related to the inefficiency of manual recording and fragmented spreadsheets, which causes redundancy and difficulty in tracking physical assets. Adopting information technology has become a strategic imperative to restructure the asset management cycle into an accountable and precise process. This study implements the Warehouse Information System (SIGUDANG) based on the web, using the Waterfall methodology. The objective is to transform manual workflows into an integrated digital system that ensures data integrity and operational efficiency. The Black-Box testing results confirm that all system functionalities are running valid (100%), particularly in the security mechanisms of CSRF Token and Role-Based Access Control (RBAC). Functionally, the system integrates Multi-Column Query, unique Manual Register Number input, and the Auto-Barcode feature. A significant achievement is the operational efficiency improvement of 45% in new asset input time, as well as the capability for instantaneous reporting through the Automatic Letter Report Generation feature (PDF/Excel) complete with the official Letterhead. Warehouse Information System SIGUDANG successfully builds a strong digital foundation for asset governance. The system is declared fit-fordeployment and contributes significantly to strengthening internal control and realizing transparency in regional asset reporting.